Managing adherence, exposure, and toxicity in oral anticancer therapies - Kazuo Kobayashi (Journal of Pharmaceutical Health Care and Sciences)
Abstract The management of adherence, exposure risk, and adverse effects in oral anticancer agents (OAAs) is essential for optimizing patient outcomes in oncology pharmacy. This review highlights key efforts to enhance adherence, reduce occupational exposure, and improve adverse effect management in OAA therapy. (1) Adherence management. We evaluated adherence to trifluridine/tipiracil hydrochloride (TFTD) in metastatic colorectal cancer (mCRC) patients, revealing an overall adherence rate of 85.0%. Common factors affecting adherence included nausea, vomiting, and cancer-related pain. Pharmacist-led interventions, including antiemetic therapy and patient education, significantly improved compliance. (2) Exposure risk management. A study on spill kit usage found that 91.7% of incidents involved nurses, with most spills occurring in hospital wards. Following a medical safety workshop, compliance with personal protective equipment (PPE) protocols improved to 100%. These findings emphasize the need for continuous safety training and enhanced spill management protocols. (3) Adverse effect management. We examined regorafenib-induced adverse effects, particularly hand-foot skin reaction (HFSR) and hypothyroidism. HFSR occurred in 81.4% of patients, with severe cases (≥ Grade 2) associated with prolonged survival. Routine thyroid function monitoring was essential, as 42.8% of patients developed thyroid dysfunction, with 5.7% requiring hormone replacement therapy. Early intervention and supportive care strategies improved treatment tolerability. This review underscores the importance of pharmacist-driven interventions in enhancing adherence, ensuring occupational safety, and managing adverse effects. Continued research and collaboration are essential to optimize OAA-based therapy and improve patient care in oncology pharmacy.